Improved squalene production through increasing lipid contents in Saccharomyces cerevisiae - Wei, Liu‐Jing; Kwak, Suryang; Liu, Jing‐Jing; Lane, Stephan; Hua, Qiang; Kweon, Dae‐Hyuk; Jin, Yong‐Su (Biotechnology and bioengineering, 2018)
Squalene, a valuable acyclic triterpene, can be used as a chemical commodity for pharmacology, flavor, and biofuel industries. Microbial production of squalene has been of great interest due to its limited availability, and increasing prices extracted from animal and plant tissues. Here we report genetic perturbations that synergistically improve squalene production in Saccharomyces cerevisiae. As reported previously, overexpression of a truncated HMG‐CoA reductase 1 (tHMG1) led to the accumulation 20‐fold higher squalene than a parental strain. In order to further increase squalene accumulation in the tHMG1 overexpressing yeast, we introduced genetic perturbations—known to increase lipid contents in yeast—to enhance squalene accumulation as lipid body is a potential storage of squalene. Specifically, DGA1 coding for diacylglycerol acyltranferase was overexpressed to enhance lipid biosynthesis, and POX1 and PXA2 coding for acyl‐CoA oxidase and a subunit of peroxisomal ABC transporter were deleted to reduce lipid β‐oxidation. Simultaneous overexpression of tHMG1 and DGA1 coding for rate‐limiting enzymes in the mevalonate and lipid biosynthesis pathways led to over 250‐fold higher squalene accumulation than a control strain. However, deletion of POX1 and PXA2 in the tHMG1 overexpressing yeast did not improve squalene accumulation additionally. Fed‐batch fermentation of the tHMG1 and DGA1 co‐overexpressing yeast strain resulted in the production of squalene at a titer of 445.6 mg/L in a nitrogen‐limited minimal medium. This report demonstrates that increasing storage capacity for hydrophobic compounds can enhance squalene production, suggesting that increasing lipid content is an effective strategy to overproduce a hydrophobic molecule in yeast. This study focused on the genetic perturbations eliciting improved lipid production and enhanced squalene accumulation in Saccharomyces cerevisiae. The engineered strains, with simultaneous overexpression of tHMG1 and DGA1 coding for rate‐limiting enzymes in the mevalonate and lipid biosynthesis pathways, showed over 250‐fold higher squalene accumulation than a control strain. The results indicated that increasing storage capacity for hydrophobic compounds enhances squalene production.